Influence of co-morbid fibromyalgia on disease activity measures and response to tumour necrosis factor inhibitors in axial spondyloarthritis: results from a UK national register. (20th July 2018) - Macfarlane, Gary J; MacDonald, Ross I R; Pathan, Ejaz; Siebert, Stefan; Gaffney, Karl; Choy, Ernest; Packham, Jon; Martin, Kathryn R; Haywood, Kirstie; Sengupta, Raj; Atzeni, Fabiola; Jones, Gareth T
Abstract: Objective: To quantify the extent to which co-morbid FM is associated with higher disease activity, worse quality of life (QoL) and poorer response to TNF inhibitors (TNFis) in patients with axial SpA. Methods: A prospective study recruiting across 83 centres in the UK. Clinical information and patient-reported measures were available, including 2011 criteria for FM. Multivariable linear regression was used to model the effect of meeting the FM criteria on disease activity, QoL and response to TNFis. Results: A total of 1757 participants were eligible for analyses, of whom 22.1% met criteria for FM. Those with co-morbid FM criteria had higher disease activity [BASDAI average difference FM + − FM − 1.04 (95% CI 0.75, 1.33)] and worse QoL [Ankylosing Spondylitis Quality of Life score difference 1.42 (95% CI 0.88, 1.96)] after adjusting for demographic, clinical and lifestyle factors. Among 291 participants who commenced biologic therapy, BASDAI scores in those with co-morbid FM were 2.0 higher at baseline but decreased to 1.1 higher at 12 months. There was no significant difference in the likelihood of meeting Assessment of SpondyloArthritis international Society 20 criteria at 12 months. Less improvement in disease activity and QoL over 3 months of TNFi therapy was most strongly related to high scores on the FM criteria symptom severity scale component. Conclusion: Fulfilling criteria for FM has a modest impact on the assessment of axial SpA disease activity and QoL and does not significantly influence response to biologic therapy. Those with a high symptom severity scale on FM assessment may benefit from additional specific management for FM.